Matthew - Duran, Nicole Wilkinson; Grimshaw, James P., 1963- (Minneapolis Fortress Press, 2013)
"The Texts @ Contexts series gathers scholarly voices from diverse contexts and social locations to bring new or unfamiliar facets of biblical texts to light. Matthew sheds new light from new perspectives on themes in the Gospel including community; land, labor, and Empire; children, parents, and families; health and disabilities; and border-crossings. The authors challenge us to consider how we deal with cultural distances between ourselves and these ancient writings - and between one another in the contemporary world."--Book description, Amazon.com
Community and beginnings. Rereading the past : memory and identity in post-communist Croatia and the genealogy of Jesus in the Gospel of Matthew / Lidija Novakovic ; A South Africa contextual reading of Matthew 1:1-17 / Jonathan A. Draper -- Children and family. What child is this? : a contextual feminist literary analysis of the child in Matthew 2 / Sharon Betsworth ; The Canaanite woman (Matthew 15:22-28)
Includes bibliographical references and indexes
Keywords: Bible. -- Criticism, interpretation, etc; Criticism, interpretation, etc